أثر استخدام تكنولوجيا المعلومات في موثوقية نظم المعلومات المحاسبية و انعكاسها على أداء المصارف التجارية دراسة استطلاعية لآراء عينة من العاملين في بعض المصارف التجارية في محافظة السليمانية بحث مستل من اطروحة دكتوراه - أحمد, أ.م. د.رزكار علي; سعيد, م. يعقوب احمد حمة (Sulaimani Journal for Humanities, 2023)
This research aims to highlight the role of information technology in order to improve accounting practices, which has been compulsory on banks to progress their information technologies including accounting system. Consequently, obtaining high quality financial reports, which facilitate the users for making the best decision. Contemporary information technology contributed to quantum leap in various field. One of the systems that has been affected extraordinary by information technology is accounting information systems and its relations with the banks’ duties in preparing financial statements. It is obvious that implementing information technology has significant influences on accounting information system reliability. Meanwhile, it plays an important role in treating the entered data in computer systems, which are derived from accounting documents. Then, transferring these recorded data to information, accordingly the users could utilize it in developing plans, conducting studies, and finally set suggestions and recommendations relying on treated information from the process. The vital of this study stems from the role that information technology plays in banks, particularly with tremendous development in communication and the emergence of modern technology and its consequences on accounting information reliability and commercial banks’ performance. This shed light on the relationship between techno information and the dimensions of reliability of accounting information system. The contribution in improving electronic accounting information system in Iraqi banks to ensure their ability to satisfy needs and desire of customers. This grants those researchers who deal with information development and information system.
Keywords: Keywords Information Technology; Reliability Accounting Information Systems; Bank Performance